FINANCIAL KNOWLEDGE, FINANCIAL ATTITUDE, AND FINANCIAL MANAGEMENT BEHAVIOR: SELF–CONTROL AS MEDIATING - Siswanti, Indra (The International Journal of Accounting and Business Society, 2020)
ABSTRACTPurpose — This research aims to analyze the factors influencing financial management behavior in employees of  Islamic University "45" Bekasi because financial behavior is a very important issue at this time.Design/methodology/approach — The sampling technique used for this research is purposive sampling with the total population is 305 employees and samples taken were 81 employees. The data used primary data and analyzed data using smart PLS.Findings — The results of the research state that financial knowledge has a significant effect on financial management behavior, the financial attitude has a significant effect on financial management behavior, self-control has a significant effect on financial management behavior, financial knowledge has a significant effect on self-control, the financial attitude has a significant effect on self-control, self-control mediated the partial effect of financial knowledge on financial management behavior, and self-control mediated the partial effect of financial attitudes on financial management behavior.Practical Implications — Financial knowledge does affect Indonesian people on how they manage their financial behavior and attitude.Originality/value — This research is related to the behavior of Indonesian people who tend to think short-term and tend to have a consumptive life pattern so that it often happens where someone with enough income but still has financial problems.Keywords Financial knowledge, financial attitude, self-control, financial management behaviorPaper Type research paper (case study)